REGIONAL REGULATIONS REVIEW IN REALIZING DEMOCRATIC REGIONAL GOVERNMENT: A CONCEPTUAL APPROACH - ANDI BAU INGGIT AR (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Quality local regulations mean that the legal product is subject to material and technical preparation in accordance with the provisions of the legislation, can solve problems and answer the needs of the community. Good regional regulation should reflect the philosophical aspects related to the principle of justice, sociological relating to the expectation that the regional regulation formed is the desire of the local community, and juridical is related to ensuring legal certainty. One of the controls on regional regulations is the testing of Regional Regulations conducted by judicial review or executive review, or legislative review. The problem is that there are many local regulations that are no longer relevant to current regulations and conditions, conflict with one another, and several other problems in the administration of local government. The research method used is the normative research method, with a conceptual approach. The absence of the concept of testing local regulations in the implementation of the democratic regional government to become a standard testing regional regulations, as a form of supervision of the formation of local regulations. Formers of Regional Regulations namely regional governments together with the Regional People's Representative Assembly (Dewan Perwakilan Rakyat Daerah/DPRD) pay less attention to regional conditions and the provisions of higher legislation in the process of forming Regional Regulations, in addition, the central government informing policies related to regional regulations testing does not stipulate provisions that explicitly regulate any subject/the institution authorized to test regional regulations in order to create good laws and regulations, so that if these conditions continue to occur, it will lead to the implementation of undemocratic local government, therefore it is necessary to conceptualize the ideal testing of regional regulations in the implementation of local government that is democratic.